2012
DOI: 10.2319/081011-506.1
|View full text |Cite
|
Sign up to set email alerts
|

Periodontopathogens around the surface of mini-implants removed from orthodontic patients

Abstract: Objective: To verify if mini-implant mobility is affected by the presence of periodontopathogens, frequently associated with peri-implantitis. Materials and Methods: The surfaces of 31 mini-implants used for skeletal anchorage in orthodontic patients were evaluated. Polymerase chain reaction was used for identification of the presence of DNA from three different periodontopathogens (P. intermedia [Pi ], A. actinomycetemcomitans [Aa], and P. gingivalis [Pg]) in 16 mini-implants without mobility (control group) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 22 publications
3
24
2
Order By: Relevance
“…In the same way as for periodontal disease, the contamination of peri‐implant tissues by pathogenic bacteria contributes for loss of secondary stability of orthodontic mini‐implants. However, as demonstrated hereby and by other authors (Tortamano et al, ), the presence of microorganisms alone is not sufficient to cause implant failure. Other factors should be considered to increase the success rate orthodontic mini‐implants, namely load applied to the mini‐implants (Estelita et al, ), placement technique, type of mini‐implant (self‐tapping or self‐drilling) (Estelita et al, ; Wilmes and Drescher, ), insertion torque, mini‐implant length and diameter (Antoszewska et al, ; Pithon et al, ; Wilmes et al, ), cortical bone thickness (Wilmes and Drescher, ), latency period before loading (Motoyoshi, ; Motoyoshi et al, ) versus immediate loading before 3 weeks of healing (Zhao et al, ) and insertion site (maxilla or mandible) (Wu et al, ).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In the same way as for periodontal disease, the contamination of peri‐implant tissues by pathogenic bacteria contributes for loss of secondary stability of orthodontic mini‐implants. However, as demonstrated hereby and by other authors (Tortamano et al, ), the presence of microorganisms alone is not sufficient to cause implant failure. Other factors should be considered to increase the success rate orthodontic mini‐implants, namely load applied to the mini‐implants (Estelita et al, ), placement technique, type of mini‐implant (self‐tapping or self‐drilling) (Estelita et al, ; Wilmes and Drescher, ), insertion torque, mini‐implant length and diameter (Antoszewska et al, ; Pithon et al, ; Wilmes et al, ), cortical bone thickness (Wilmes and Drescher, ), latency period before loading (Motoyoshi, ; Motoyoshi et al, ) versus immediate loading before 3 weeks of healing (Zhao et al, ) and insertion site (maxilla or mandible) (Wu et al, ).…”
Section: Discussionsupporting
confidence: 65%
“…The factors and mechanisms that lead to loss of stability of orthodontic mini‐implants are not yet fully elucidated, but possible causes include: incorrect placement, proximity with dental roots, lack of primary stability, and contamination of the device with pathogenic bacteria. Different studies have shown that mini‐implants with signs of peri‐implantitis contain subgingival microbiota very similar to that found in periodontal disease, with progressive breakdown of soft and hard peri‐implant tissues (Chen et al, ; Mombelli et al, ; Tortamano et al, ). However, the results of the present study were not supportive to existence of a relationship between loss of stability and presence of microorganisms on the surface of mini‐implant components (head, transmucosal profile, and body).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Clinically, the removal of TADs is considered minimally invasive and the small, transient intraoral open wounds created by their removal are assumed to undergo spontaneous healing . However, fairly high risks of irreversible soft tissue scarring, sinus tracts accompanied by inflammation, and disturbed wound healing due to bony sequestra have been reported at TAD removal sites, with periodontal pathogens commonly detected in retrieved TADs . This raises concerns about possible incomplete healing after TAD removal.…”
Section: Introductionmentioning
confidence: 99%